Sinergismo para la solución de problemas ambientales: remediación de fuentes hídricas mediante el empleo de bases de schiff (2020)
The sources of drinking water, necessary to guarantee the health of living beings and the environment, are increasingly scarce. This serious problem requires the develop-mentof new eco-friendly technologies which allow the heavy metals monitoring, prevention and, especially, contaminated water sources remediation. Understanding the necessity to lead the research activities towards the design of newmaterials whichcould be promissory in retaining or facilitating pollutants removal with higher efficiency and effectiveness, this article presents some of the recent advances respect to the development of novel methods for water remediation employing Schiff bases, a family of molecules of great relevance in chemistry. The presented results allow to demonstrate both, the chelating and catalytic activities, and especially, the potential application for environmental purposes of Schiff bases; considering the latter, as an incipient research to explore still in Science and Engineering.